PENERAPAN MODEL PEMBELAJARAN KOOPERATIF MELALUI TGT (TEAMS GAMES TOURNAMENT) UNTUK MENINGKATKAN HASIL BELAJAR DAN PEMBENTUKAN KARAKTER ISLAMI SISWA: RESEARCH BASE DI SEKOLAH - Larasati, Dinda Kenanga; Faizin, Moh. (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the fact that during learning, not all students have the same learning power and active involvement, resulting in significant differences in learning outcomes, in addition, many students still choose their own group mates in socializing or forming groups, resulting in homogeneous groups. Therefore, the researcher conducted this study aimed to analyze the application of the Teams Games Tournament (TGT) type cooperative learning model in improving learning outcomes and the formation of Islamic character of students in the subject of Islamic Religious Education, the material of avoiding backbiting and carrying out tabayun class VII-B at SMPN 1 Krian. This research method uses a descriptive qualitative approach with classroom observation methods. The results of these observations indicate that class VII-B students carry out learning with the TGT type which is considered effective in improving student learning outcomes and forming their Islamic character with honesty, cooperation, responsibility and mutual respect.